Stock market volatility and trading volume: A special case in Hong Kong with stock connect turnover - Brian Sing Fan Chan; Andy Cheuk Hin Cheng; Alfred Ka Chun Ma (Journal of Risk and Financial Management, 2018)
The cross-boundary Shanghai-Hong Kong and Shenzhen-Hong Kong Stock Connect provides a special data set to study the dynamic relationships among volatility, trading volume and turnover among three stock markets, namely Shanghai, Shenzhen, and Hong Kong. We employ the Granger Causality test with the vector autoregressive model (VAR) to examine whether Stock Connect turnover contributes to future realized volatility and market volume of these three markets. Our results support the evidence of causality from Stock Connect turnover to market volatility and trading volume. The finding of this causality is consistent with the implication of the sequential information arrival model in the literature.
Keywords: 330; Volatility-Volume; realized volatility; Stock Connect